Plant fibres as ice cream stabilisers - Neville, Michelle E (2017)
Over recent decades, the push in consumer trends towards the production of clean label, functionalised foods has resulted in food manufacturers looking towards plant fibres as a source of alternative stabilisers. Not only can plant fibres be considered as sustainable ingredients but they are also able to, due to the functional properties that they possess, allow the food manufacturer to meet the functional foods demand. Plant fibres were assessed as an alternative source of ice cream stabilisers. Firstly, a selection of plant fibres of different plant origin where characterised and their functional properties in suspension were determined to identify which plant fibres provided the most potential as ice cream stabilisers. These fibres were then incorporated into ice cream formulations and it was found that their addition had no impact on the correct microstructure formation. Heat shock is the process whereby ice cream is stored in inappropriate temperature conditions or experiences breaks in the frozen-chain. Such drastic changes in temperature can alter the microstructure of ice cream reducing the sensory quality. Hydrocolloids are added to ice cream formulations to prevent such sensory deteriorations and for plant fibres to be a suitable source of alternative stabilisers they too must be able to prevent such deteriorations. It was found that the ability to control ice recrystallisation was dependent on the water binding capacity of the fibre, which in turn was related to the total fibre content. However, under heat shock conditions, this ability to control the rate of ice recrystallisation was largely dependent on the freeze-thaw stability of the fibre. It was found, in comparison to a hydrocolloid stabilised sample, that plant fibres have no impact on the rate of ice cream meltdown, nor the final mass loss, but could inhibit the time to first drip due to the ability of plant fibres to behave as ‘sponges’, absorbing the water from melting ice and hindering the rate of drainage by the formation of a fibrous network with the matrix phase. Higher apparent viscosities were also associated with improved meltdown properties. However, when plant fibres were co-stabilised with guar gum at the concentrations studied, improvements in the meltdown properties and control over microstructural deteriorations were observed but samples became undesirably over texturised. Sensory analysis was performed to determine the impact of plant fibres on the sensory perception of ice cream as well as the ability of plant fibres to retain sensory quality under heat shock conditions. It was found that plant fibres impart a powdery and mouth drying sensation due to the presence of insoluble fibre particles. Plant fibres of a high enough total fibre content were also found to be able to impart the correct mouthfeel properties in ice cream. Under heat shock conditions, it was found that the more freeze-thaw stable fibres were able to control increases in the iciness perception. However, plant fibres were not found to be able to control the sensory changes that are related to the structure of air, as cryo-Scanning Electron Microscopy imaging identified that plant fibres behave as anti-foams in ice cream formulations under temperature cycling conditions.